Determination of Specific Emission Factors of Residential for Carbon Footprint Estimation and Mapping in Banyuwangi District - Layli Yuliana (Purifikasi, 2016)
Increasing concentration of CO2 in the atmosphere occurred due to human activities, one of which is the residential sector. In an effort to overcome the problem of increased concentrations of greenhouse gases, the Government of Indonesia launched the first step action plan to mitigate climate change by doing GHG inventory in accordance with the IPCC guidelines. To increase the accuracy in conducting an inventory, each country was encouraged to draw up specific emission factors. This study aims to determine the residential sector of specific emission factors and analyze the distribution of emissions by mapping the carbon footprint. Calculation method was using the IPCC. Activity data was fuel for cooking in urban and rural areas. The results of the questionnaire showed a different pattern of household fuel consumption in urban and rural areas, households in urban areas generally use LPG, whereas in the rural areas wear LPG and firewood. From the results obtained by analysis, the value of specific emission factor of fuel use for cooking in urban areas 0,3855 tons of CO2/ household.year, in rural areas 1,7776 tons of CO2/household.year. The result of calculation and mapping shows higher carbon footprint of fuel in rural areas due to the use of firewood.